2004
DOI: 10.1007/s11661-004-0144-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative characterization of the three-dimensional microstructure of polycrystalline Al-Sn using X-ray microtomography

Abstract: Characterizing the three-dimensional topology of grain-boundary networks in polycrystalline materials is a crucial step in the modeling of properties that depend on the sample microstructure. Using absorptioncontrast X-ray microtomography, we have carried out a large-scale microstructural characterization of polycrystalline Al doped with 2 at. pct Sn, which is immiscible in Al in the solid state. The segregation of Sn to the grain boundaries imparts a strong contrast in X-ray attenuation that can be reconstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 54 publications
(67 reference statements)
2
38
0
Order By: Relevance
“…Various experimental techniques are available for microstructural characterization [25,26,27,28,29,71,72,73] and their output is sometimes used as input for finite element (FE) analysis [74,75,48,49]. However a complete 3D reconstruction still remains a challenging task.…”
Section: Artificial Microstructure Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Various experimental techniques are available for microstructural characterization [25,26,27,28,29,71,72,73] and their output is sometimes used as input for finite element (FE) analysis [74,75,48,49]. However a complete 3D reconstruction still remains a challenging task.…”
Section: Artificial Microstructure Generationmentioning
confidence: 99%
“…The Voronoi tessellations have been consistently adopted for representing polycrystalline materials at the grain scale [77,78,79]. Although it has been shown that they slightly misestimate some polycrystalline microstructural distributions [25,80], they have however been widely successfully employed for modelling purposes [5,81,80,82,83,84,85,86,70]. In any case, the Voroni tessellations have the advantage of being analytically defined and simple to generate.…”
Section: Artificial Microstructure Generationmentioning
confidence: 99%
“…An alternative strategy, based on the use of level set functions for the generation of meshes with anisotropic refinement, was proposed by Resk et al 142 , who also extended their technique to remeshing procedures in case of problems involving large deformations. The meshing of experimentally reconstructed microstructures has been accomplished in several studies 7,118,112,120,121,17 Bhandari and Ghosh et al 119,143 developed a sophisticated methodology for meshing 3D polycrystalline microstructures, generated with a DB FIB-SEM system. The grains are segmented as a collection of voxels using crystallographic orientation data and the surface topology is smoothed using polynomial and NURBS functions.…”
Section: Microstructure Meshing and Remeshingmentioning
confidence: 99%
“…Their microstructure, at the grain scale, is characterized by the grain morphology, size distribution, anisotropy and crystallographic orientation, by the presence of flaws and porosity and by physical and chemical properties of the intergranular interfaces 6 , which also have a direct effect on the initiation and evolution of damage. The behavior of polycrystalline materials at the microscale can be studied using experimental 7,8,9,10,11,12,13,14,15 and computational techniques 4,16,17 . Much research has been carried out for developing numerical models for the analysis of polycrystalline microstructures and their failure processes.…”
Section: Introductionmentioning
confidence: 99%
“…Their microstructure, at the grain scale, is characterized by grains morphology, size distribution, anisotropy and crystallographic orientation, by the presence of flaws and porosity and by physical and chemical properties of the intergranular interfaces [6], which have direct influence on the initiation and evolution of damage. Polycrystalline microstructures have been studied using experimental [7,8,9,10,11,12,13,14,15] and computational techniques [4,16,17]. Much research has been carried out for developing numerical models for polycrystalline microstructures and their failure processes.…”
Section: Introductionmentioning
confidence: 99%